2013
DOI: 10.3109/02770903.2013.834932
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers in elderly asthma

Abstract: Covilhã, Junho de 2013Serum Biomarkers in Elderly Asthma ii Serum Biomarkers in Elderly Asthma iii "Victoria discentium, gloria docentium" Serum Biomarkers in Elderly Asthma iv Acknowledgements À minha orientadora, a Professora Doutora Olga Lourenço, um profundo agradecimento por toda a orientação, dedicação, e paciência que para comigo demonstrou, nos bons e nos maus momentos. Um grande obrigado por todos os segredos de citometria que comigo partilhou, permitindo-me ver e compreender aquilo que realmente pode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 82 publications
(57 reference statements)
0
31
0
Order By: Relevance
“…Chitinase 1 plays a role as inflammatory and profibrotic molecule in both diseases, suggesting that it may be a useful disease biomarker and indicator of atherosclerotic plaque formation, as well as in pulmonary granulomatous inflammation [34][35][36] . Human chitotriosidase concentrations, related to lipid-laden macrophages in human atherosclerotic vessel walls [29] , generally increase with age and depend on accumulation of lipidfilled macrophages during progression of atherosclerosis [37,38] . Macrophage accumulation localized in the supra-aortic and coronary vessels is associated with increased serum CHIT1 activity, which reflects the state of activation of macrophages [29] ( Fig.…”
Section: Chitotriosidase In Atherosclerosis and Sarcoidosismentioning
confidence: 99%
“…Chitinase 1 plays a role as inflammatory and profibrotic molecule in both diseases, suggesting that it may be a useful disease biomarker and indicator of atherosclerotic plaque formation, as well as in pulmonary granulomatous inflammation [34][35][36] . Human chitotriosidase concentrations, related to lipid-laden macrophages in human atherosclerotic vessel walls [29] , generally increase with age and depend on accumulation of lipidfilled macrophages during progression of atherosclerosis [37,38] . Macrophage accumulation localized in the supra-aortic and coronary vessels is associated with increased serum CHIT1 activity, which reflects the state of activation of macrophages [29] ( Fig.…”
Section: Chitotriosidase In Atherosclerosis and Sarcoidosismentioning
confidence: 99%
“…Biomarkers facilitate early diagnosis, prognosis and identification and hence are potential therapeutic targets [8][9][10][11]. Serum IgE levels, CBC/blood eosinophils counts, Fractional Exhaled Nitric Oxide (FENO) levels, and sputum eosinophils counts are widely used to diagnose asthma [12][13][14][15][16][17][18]. None of these can be considered as established biomarker(s) of asthma [19].…”
Section: Introductionmentioning
confidence: 99%
“…YKL-40 is essential for IL-13 mediated Th2 inflammation and related with antigen sensitization and IgE induction in animal models (9), but the relations between YKL-40 and markers of Th2 inflammation such as total serum IgE and peripheral blood eosinophils are controversial in patients with asthma. (8,24). Current study suggests that serum levels of YKL-40 were different according to FEV 1 but not specific diseases.…”
Section: Discussionmentioning
confidence: 60%
“…Meanwhile since there were no direct evaluations for airway inflammation, there was possibility that asthmatics with neutrophilic Th1 inflammation which is pathophysiologically more similar to COPD were enrolled in this study. Asthma with neutrophilic Th1 inflammation is a less common phenotype and usually known to be associated with low FEV 1 and characteristic of older patients with a late onset of the disease (24). In contrast, enrolled patients in this study were young and had relatively normal FEV 1 , and furthermore they showed relations between total IgE and airway hyperresponsiveness which is closely related with Th2 inflammation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation